Generational accounting in general equilibrium - Hans Fehr; Laurence J. Kotlikoff (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 1995)
This paper shows how changes in generational accounts relate to the generational incidence of fiscal policy. To illustrate the relationship, it uses the Auerbach-Kotlikoff Dynamic Life-Cycle Simulation Model to compare policy-induced changes in generational accounts with actual changes in generations' utilities. The paper considers a wide ränge of policies in closed and small open economies as well as economies with and without capital adjustment costs. In general, changes in generational accounts appear to provide fairly good approximations to generations' actual changes in utilities. The approximations are better for living generations. They are worse for policies that involve significant changes in the degree of tax progessivity and for economies with sizable capital adjustment costs. Finally, generational accounting needs to be adjusted in the case of small open economies to take into account the fact that the incidence of corporate taxation is on labor. The method of adjustment is simply to allocate changes in corporate tax revenues to generations in proportion to their changes in labor supply.
Keywords: 330